Introducing Dental Students to Clinical Patient Care: The Complete Denture Prosthodontics Transition Clinic - Lisa A. Lang, DDS, MS,1 David C. Holmes, DDS, MS,2 (Journal of Prosthodontics, 2003)
Using complete denture treatment as an introduction to clinical patient care for dental students, the purposes of the Complete Denture Prosthodontics Transition Clinic at the University of Colorado School of Dentistry are to reduce the time lapse between the preclinical complete denture prosthodontics course and the first denture patient experience, and to encourage development of student self-confidence and skills.